(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The nitration of toluene is most important route to obtain substituted aromatic intermediates viz., nitrotoluenes and dinitrotoluenes for the production of speciality chemicals mainly after reduction of the nitro group. In the conventional nitration, however, the production of the ortho isomer exceeds that of the para isomer. To overcome this limitation, nitrations using solid acids as catalysts are receiving increased attention. Solid super acid catalysts like polystyrene sulfonic acid, perfluorinated sulfonic acid (Nafion H) with HNO3 or its metal salts, mixed anhydrides or nitrate esters catalyzed by H2SO4 and nitrations under essentially neutral conditions using N-nitropyridinium, N-nitroquinolium salts, nitro and nitrite onium salts have been reported to enhance the reactivity of the nitrating agent.